2020
DOI: 10.3389/fmicb.2020.02088
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanisms of Positive Microbial Interactions That Benefit Lactic Acid Bacteria Co-cultures

Abstract: Microorganisms grow in concert, both in natural communities and in artificial or synthetic co-cultures. Positive interactions between associated microbes are paramount to achieve improved substrate conversion and process performance in biotransformation and fermented food production. The mechanisms underlying such positive interactions have been the focus of numerous studies in recent decades and are now starting to be well characterized. Lactic acid bacteria (LAB) contribute to the final organoleptic, nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 156 publications
1
53
0
1
Order By: Relevance
“…Even if, ultimately, co-culturing in the laboratory and/or in appropriate model systems is the only way to obtain in-depth knowledge on the nature of interactions (Cosetta and Wolfe, 2019;D'Souza et al, 2018;Wolfe et al, 2014), the wealth of data provided by metataxonomic, metagenomic and metabolomics approaches provides ample opportunity to mine for microbial association networks and metabolic networks (Layeghifard et al, 2017;Liu et al, 2020;Röttjers and Faust, 2018). Microbial interactions in cheese and in other fermented foods have been the subject of recent comprehensive reviews (Blaya et al, 2017;Canon et al, 2020;Gobbetti et al, 2018;Mayo et al, 2021). A schematic, and possibly oversimplified representation of interactions (parasitism, commensalism, amensalism, competition, protocooperation) occurring in an idealized surface ripened cheese is shown in Figure 1, with some of the interactions described in detail in section 1.3 and Table 1.…”
Section: Forewordmentioning
confidence: 99%
See 3 more Smart Citations
“…Even if, ultimately, co-culturing in the laboratory and/or in appropriate model systems is the only way to obtain in-depth knowledge on the nature of interactions (Cosetta and Wolfe, 2019;D'Souza et al, 2018;Wolfe et al, 2014), the wealth of data provided by metataxonomic, metagenomic and metabolomics approaches provides ample opportunity to mine for microbial association networks and metabolic networks (Layeghifard et al, 2017;Liu et al, 2020;Röttjers and Faust, 2018). Microbial interactions in cheese and in other fermented foods have been the subject of recent comprehensive reviews (Blaya et al, 2017;Canon et al, 2020;Gobbetti et al, 2018;Mayo et al, 2021). A schematic, and possibly oversimplified representation of interactions (parasitism, commensalism, amensalism, competition, protocooperation) occurring in an idealized surface ripened cheese is shown in Figure 1, with some of the interactions described in detail in section 1.3 and Table 1.…”
Section: Forewordmentioning
confidence: 99%
“…Microbial interactions in cheese and in other fermented foods have been the subject of recent comprehensive reviews (Blaya et al, 2017; Canon et al, 2020; Gobbetti et al, 2018; Mayo et al, 2021). A schematic, and possibly oversimplified representation of interactions (parasitism, commensalism, amensalism, competition, protocooperation) occurring in an idealized surface ripened cheese is shown in Figure 1, with some of the interactions described in detail in section 1.3 and Table 1.…”
Section: Forewordmentioning
confidence: 99%
See 2 more Smart Citations
“…Khan et al (2018) [ 19 ] reported that LAB-fermented dried longan contained higher phenolic and flavonoid contents and antioxidant capacities compared to unfermented dried longan. Pharmacological studies of LAB have been reported to convince the improvement of therapeutic effects, e.g., diarrhea, constipation and colitis [ 20 , 21 , 22 ]. Furthermore, LAB co-cultures could produce added value according to the increase in food quality, such as flavor and texture, and enhance functionality [ 23 ].…”
Section: Introductionmentioning
confidence: 99%